Nüks Kasık Fıtığında Kitle Halinde Spontan Redüksiyon: Olgu Sunumu - Ağaoğlu, Nazım; Yüce, Yusuf; Türkyılmaz, Serdar; Arslan, Mithat K. (Fırat University, 2003)
Amaç: Fıtıkların kitle halinde redüksiyonu, fıtık kesesi ve barsak muhtevasıyla birlikte strangülasyon olmaksızın preperitoneal aralığa yer değiştirmesiyle karakterize nadir görülen bir durumdur. Gereç ve yöntem: Akut batın klinik tablosuyla müracaat eden spontan kitle halinde redükte olmuş bir nüks inguinal hemi vakasını takdim etmekteyiz. Laparatomide, preperitoneal alana kitle halinde redükte olan fıtık kesesi içinde strangüle ince barsak ansı olduğu görüldü. Sonuç: Barsak ansı serbestleştirildikten sonra anterior fıtık tamiri yapıldı. Muayenede fıtık şişliğinin kaybından sonra hastalarda obstrüksiyon semptom ve bulgularının devam etmesi veya ortaya çıkması kitle halinde redüksiyon ihtimalini akla getirmelidir.

Aim: Reduction en masse of a hernia is a rare clinical entity characterized by displacement of a hernia mass formed of hernial sac and its bowel contents to preperitoneal space without relief of strangulation. Materials and method: A very rare case of spontaneous reduction en masse of recurrent inguinal hernia presented with clinical features of acute abdomen. Explorative laparatomy revealed a loop of small intestine strangulated by the peritoneal ring of the hernial sac which had been reduced en masse to the preperitoneal space. Conclusions: The strangulated small intestine was released and anterior hernial repair was performed. Persistent of symptoms and signs of intestinal obstruction after recent disappearance of the hernial swelling in patients with recurrent groin hernias should alert the physician to consider possibility of reduction en masse of the hernia.
A Case Report: Spontaneous Reduction En Masse of Recurrent Inguinal Hernia